Psychometric properties of a sport motivation scale - J. F. Guzmán; E. Carratalá; Á. García-Ferriol; V. Carratalá (Asociación Española de Ciencias del Deporte, 2010)
Different types of motivation are a topic of study to both psychologists and sport psychologists, and their assessment as been one area of interest. "Sport Motivation Scale" (SMS), (Pelletier et al., 1995) was created to measure intrinsic and extrinsic motivation, and amotivation, to sport participation. The psychometric properties of French and English scales have been analysed, with no conclusive results. Spanish version (López, 2000) did not validate factorial structure proposed by original authors. In this study we analyzed a new Spanish version of the scale, translated from English, with a sample of 477 Secondary Education athletes, using SEM (Structural Equation Modelling). Results showed a relative support to reliability and validity of SMS, similar to the study of Martens y Webber (2002). KEY WORDS: Intrinsic motivation, psychometric properties, confirmatory factorial analysis.